Carbonate apatite nephrolithiasis associated with Corynebacterium urealyticum urinary tract infection in a dog. Issue 5 (May 2014) - Fleischhacker, SN; Horstmann, C; Hartmann, K; Schubert, S; Dorsch, R
<x xml:space="preserve">Abstract</x> Background Urinary tract infections caused by Corynebacterium urealyticum are uncommon in veterinary medicine. Encrusted cystitis, encrusted pyelitis and uroliths have been described as complications in humans, but only encrusted cystitis and cystoliths have been reported in dogs so far. Because C. urealyticum is usually resistant to all standard antibacterial drugs, antimicrobial treatment and elimination of this microorganism are challenging. Case report An 11‐month‐old female spayed mixed‐breed dog was evaluated because of a C. urealyticum urinary tract infection, mineralisation within both renal pelvises and failure of antimicrobial treatment. Physical examination, haematology and biochemistry were unremarkable. Radiographic and ultrasonographic examinations confirmed bilateral nephrolithiasis. Voided uroliths were composed of 100% carbonate apatite. Urinalysis was indicative of bacterial infection. Aerobic culture of the urine and 16S rRNA sequencing identified significant growth of C. urealyticum and susceptibility testing revealed sensitivity to only vancomycin and linezolid. Conclusion Treatment with the oxazolidinone antibacterial, linezolid, in combination with a urine‐acidifying diet resulted in elimination of this multiresistant microorganism and complete resolution of nephrolithiasis.